LITERATUR REVIEW: PROGRAM MOTHER SMART GROUNDING (MSG) DALAM PENANGANAN GIZI STUNTING - Ni Ketut Erawati (Jurnal Kesehatan dr. Soebandi, 2020)
Stunting is a chronic nutritional problems that cause children fail to grow than other children his age. This research aims to analyze the articles related to stunting and handling. The design used is the literature review is to collect related articles nutritional stunting problem. Results of the study showed stunting handling is performed in two ways namely through specific nutrition intervention and nutritional interventions. One of the efforts that included nutrition intervention in sensitive is health education. Proposed behavior change is urgently needed to improve the knowledge and capabilities of the mother in the prevention of stunting, one of which is the program a Smart Mother Grounding (MSG). The program has an advantage because of the MSG 1) is an education package in the form of a conventional extension programs, Division of booklets, and demonstration of healthy snacks made from local food, 2) focus prevention not only fixed on 1000 PPC but rather aimed at the mom to prepare for the growth and development of children early on. Through the Program Mother Smart Grounding are expected to give a meaningful contribution towards the prevention of stunting. Key words: Stunting, Preventive, Mother Smart Grounding Program